The Internet and Political Participation of Indonesian Students in Taiwan - Albertus Magnus Prestianta (Ultimacomm: Jurnal Ilmu Komunikasi, 2014)
This study examined how Internet through online news media is used to influence political participation and political efficacy. Scholars believe that the existence of Internet could have a significant impact on broadening political participation and political efficacy. This research is written based on the quantitative approach. Questionnaire items were employed to find out the relationships between online news media, political participation and political efficacy. The samples used in this research are Indonesian students in Taiwan. As predicted, the findings indicated that Internet usage, particularly online news media, was positively associated with higher levels of political participation and also political efficacy among Indonesian students in Taiwan. Keywords: Indonesian, the Internet, online news media, political efficacy, politicalparticipation.